Diagnosis and Management of Fingolimod-Associated Macular Edema - Wang, Chunjiang; Deng, Zhenzhen; Song, Liying; Sun, Wei; Zhao, Shaoli (Frontiers in Neurology, 2022)
Objectives: To investigate the clinical features, treatment and prognosis of fingolimod-associated macular edema (FAME), and to provide reference for its rational use. Methods FAME-related case reports were included for a pooled analysis by searching Chinese and English databases from 2010 to November 31, 2021. Results: The median age of the 38 patients was 51 years (range 21, 67), including 29 females and 9 males. The most common complaints of 53 eyes were blurred vision (17 cases) and decreased visual acuity (13 cases) with a median onset time of 3m (range 0.03, 120), including left eye (13 cases), right eye (9 cases) and both eyes (15 cases). Forty-five eyes had near normal visual acuity (20/12-20/60), and the remaining 8 eyes had moderate to severe visual impairment (20/80 - 20/500),. Optical coherence tomography scans and fundus fluorescein angiography showed macular thickening, foveal cysts, subretinal fluid, and dye leakage. Complete resolution of ME in 50 eyes and recovery of visual acuity in 45 eyes at a median time of 2 m (range 0.25, 24) after discontinuation of fingolimod or administration of topical therapy. Conclusions: Macular edema is a known complication of fingolimod. All patients using fingolimod require regular eye exams, especially those with a history of diabetes, uveitis, and undergoing cataract surgery.